2021
DOI: 10.1101/2021.01.08.21249434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of algorithm-based versus single-item diagnostic measures of anxiety and depression disorders in the GLAD and COPING cohorts

Abstract: BackgroundResearch to understand the complex aetiology of depressive and anxiety disorders often requires large sample sizes, but this comes at a cost. Large-scale studies are typically unable to utilise “gold standard” phenotyping methods, instead relying on remote, self-report measures to ascertain phenotypes.AimsTo assess the comparability of two commonly used phenotyping methods for depression and anxiety disorders.MethodParticipants from the Genetic Links to Anxiety and Depression (GLAD) Study (N = 37,419… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…limitations relating to concerns around accuracy and memory of reporting. However, the GAD-7 has been shown to have good face validity for identifying individuals with anxiety disorders (Spitzer et al, 2006) and self-reported anxiety diagnoses have been shown to have reasonable agreement (76.7%) with an algorithm-based measure of anxiety disorders (Davies et al, 2021). Agreement for selfreported anxiety diagnoses was lower when looking at specific anxiety disorders separately, which was avoided in the current article.…”
Section: Limitationsmentioning
confidence: 86%
See 2 more Smart Citations
“…limitations relating to concerns around accuracy and memory of reporting. However, the GAD-7 has been shown to have good face validity for identifying individuals with anxiety disorders (Spitzer et al, 2006) and self-reported anxiety diagnoses have been shown to have reasonable agreement (76.7%) with an algorithm-based measure of anxiety disorders (Davies et al, 2021). Agreement for selfreported anxiety diagnoses was lower when looking at specific anxiety disorders separately, which was avoided in the current article.…”
Section: Limitationsmentioning
confidence: 86%
“…(for a full list of response options, see Table S3). Single-item measures assessing anxiety disorder diagnosis have been shown to have reasonable agreement (76.7%) with more detailed algorithm-based assessments (Davies et al, 2021).…”
Section: Self-reported Lifetime Diagnosesmentioning
confidence: 97%
See 1 more Smart Citation